2018
DOI: 10.1128/aem.02330-17
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Transplant from Highly Feed-Efficient Donors Shows Little Effect on Age-Related Changes in Feed-Efficiency-Associated Fecal Microbiota from Chickens

Abstract: Chickens with good or poor feed efficiency (FE) have been shown to differ in their intestinal microbiota composition. This study investigated differences in the fecal bacterial community of highly and poorly feed-efficient chickens at 16 and 29 days posthatch (dph) and evaluated whether a fecal microbiota transplant (FMT) from feed-efficient donors early in life can affect the fecal microbiota in chickens at 16 and 29 dph and chicken FE and nutrient retention at 4 weeks of age. A total of 110 chickens were ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 40 publications
4
59
2
Order By: Relevance
“…2A, D, and G), which were 1.9-, 2.3-, and 4.4-fold greater than their FMT-related counterparts, respectively, suggesting that the FMT intervention effect was weaker than the UC pathological effect in microbial and metabolic reprogramming. Similarly, a recent study found that FMT from highly feedefficient donors shows little effects on age-related changes in feed efficiency-associated fecal microbiota in chickens (33). Taken together, these results suggest that host-and environment-related factors may more strongly affect host fecal microbiota and metabolism than the FMT.…”
Section: Resultsmentioning
confidence: 55%
“…2A, D, and G), which were 1.9-, 2.3-, and 4.4-fold greater than their FMT-related counterparts, respectively, suggesting that the FMT intervention effect was weaker than the UC pathological effect in microbial and metabolic reprogramming. Similarly, a recent study found that FMT from highly feedefficient donors shows little effects on age-related changes in feed efficiency-associated fecal microbiota in chickens (33). Taken together, these results suggest that host-and environment-related factors may more strongly affect host fecal microbiota and metabolism than the FMT.…”
Section: Resultsmentioning
confidence: 55%
“…Development of chicken gut microbiota in commercially hatched chickens has been well described [4,16,[56][57][58]. The first coloniser is represented by E. coli which dominates in the caecum during the first week of life.…”
Section: Development Of Gut Microbiota In Commercially Hatched Chickensmentioning
confidence: 99%
“…Interestingly, there was no effect of the FMT on residual feed intake or nutrient retention; however, in female chickens, FMT appeared to increase total feed intake and overall weight gain. This study highlights that host characteristics, such as sex, may play an important role in the effect and success of FMT administration (Siegerstetter et al, 2018).…”
Section: Fmt Use In Livestockmentioning
confidence: 83%
“…Compared to mock-transplanted controls, FMT significantly reduced the number of pigs affected by porcine circovirus associated disease, as demonstrated by a reduction in morbidity, mortality, pathology, and virus replication . In another experimental study, FMT was evaluated in young piglets as a (Siegerstetter et al, 2018) (continued on next page) modulator of immunity and as a tool to improve the response to Mycoplasma hyopneumoniae. Transplantation provided benefits to the systemic immune response of pigs, including a reduction in clinical respiratory disease and more rapid antibody production (Schachtschneider et al, 2013).…”
Section: Fmt Use In Livestockmentioning
confidence: 99%